THE EFFECTIVENESS OF DISTRICT REGULATIONS IN CONTROLLING THE CIRCULATION OF ALCOHOLIC BEVERAGES TO MINORS: (Case Study of Indramayu Regency) - Zaidan Rizky Suherman; Harmono Harmono (Hukum Responsif, 2027)
Background. The increasing circulation of alcoholic beverages among minors has become a significant legal and social concern in Indonesia, particularly in regions where local governments have enacted regulations to restrict their distribution. Aims. This study aims to examine the effectiveness of Indramayu Regency Regional Regulation Number 15 of 2006 in controlling the circulation of alcoholic beverages to minors and to identify the factors affecting its implementation. Methods. The research employed an empirical juridical approach using descriptive qualitative analysis. Primary data were collected through interviews with officials from the Indramayu Regency Civil Service Police Unit (Satpol PP) and other relevant authorities, while secondary data were obtained from legislation, legal literature, scholarly publications, and official documents. Result. The findings reveal that although the regional regulation provides a comprehensive legal framework for prohibiting the production, distribution, sale, storage, and consumption of alcoholic beverages within the regency, its implementation has not been fully effective. Enforcement activities, including routine patrols, raids, inter-agency coordination, and community reporting mechanisms, have helped control illegal alcohol distribution. However, persistent violations remain due to limited human resources, inadequate public awareness, insufficient socialization of the regulation, weak supervisory capacity, economic incentives for illegal traders, easy access to alcoholic beverages through informal vendors, and social tolerance toward alcohol consumption among adolescents. Conclusion. The study concludes that legal regulation alone is insufficient to effectively protect minors without consistent law enforcement, adequate institutional capacity, and active community participation. Implementation. Strengthening cross-sector collaboration, enhancing public legal education, improving monitoring systems, and conducting regular policy evaluations are essential to increasing the effectiveness of local regulations in preventing underage access to alcoholic beverages and promoting public safety.